MIGRATION STUDY OF RADIONUCLIDES IN A MEDITERRANEAN FOREST SOIL USING SYNTHETIC AEROSOLS (SCIENCE OF THE TOTAL ENVIRONMENT, 1994)
Radionuclide migration in a Mediterranean forest was studied in field conditions. Fresh Holm oak leaves were exposed to a synthetic aerosol including Cs-134, Sr-85 and Ag-110m, and were incubated in the original Holm oak forest in two types of cylinder: (1) cylinders in which the contaminated litter lies directly on the original F layer; (2) cylinders with an exchange resin bag inserted between the contaminated litter and the underlying F layer. The results for 232 days of incubation showed that Cs-134 presented an initial rapid leaching period, which corresponded to the fraction extracted with water from the initially contaminated leaves. Further Cs-134 release was related to litter decompostiion. Sr-85 migration was studied for only 76 days, and its behaviour appeared to be similar to Cs-134. Both radionuclides migrated within the litter leachates. After 3 months of incubation, around 70% of the initial Cs-134 was transferred to the underlying layers, mainly to the F layer. Cs-134 absorbed into the leaves was released at the same rates as K. The Ag-110m activity lost from the contaminated litter amounted to around 45% in the open cylinders, from which 15-20% was attributed to the effect of soil faunal activity. The field method proposed proved to be useful in describing radionuclide migration in situ and the mechanisms involved.